2017
DOI: 10.1016/j.ejvs.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Aorta Related and All-cause Mortality in Patients with Aortic Intramural Haematoma

Abstract: Late aorta related mortality in IMH was low whereas all-cause mortality was substantial. Aorta related mortality in IMH patients only occurs during the first year after diagnosis. Interventions after the first year are rarely necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 20 publications
2
32
9
Order By: Relevance
“…Schoenhoff et al also reported that there was no difference in mortality in patients who underwent TEVAR within and after the first 2 weeks (25% vs 29%) . Compared with Schoenhoff's study, our study showed an obviously higher mortality of TEVAR after 2 weeks (48% vs 29%) and lower mortality of TEVAR within 2 weeks (2.5% vs 25%) …”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…Schoenhoff et al also reported that there was no difference in mortality in patients who underwent TEVAR within and after the first 2 weeks (25% vs 29%) . Compared with Schoenhoff's study, our study showed an obviously higher mortality of TEVAR after 2 weeks (48% vs 29%) and lower mortality of TEVAR within 2 weeks (2.5% vs 25%) …”
Section: Discussioncontrasting
confidence: 59%
“…Schoenhoff and colleagues reported that 43% of type B IMH patients underwent TEVAR during the first 2 weeks after diagnosis because of the visualization of an entry tear and aneurysm development, and 19% patients received TEVAR after the acute phase and during the first year . Schoenhoff et al also reported that there was no difference in mortality in patients who underwent TEVAR within and after the first 2 weeks (25% vs 29%) . Compared with Schoenhoff's study, our study showed an obviously higher mortality of TEVAR after 2 weeks (48% vs 29%) and lower mortality of TEVAR within 2 weeks (2.5% vs 25%) …”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations